Ethnopharmacological uses of fauna among the people of central Punjab, Pakistan - Khan, Abdul Majid; Altaf, Muhammad; Hussain, Tanveer; Hamed, M. Haroon; Safdar, Umaira; Ayub, Amina; Memon, Zaibun-nisa; Hafiz, Adnan; Ashraf, Sana; Amjad, Muhammad Shoaib; Majeed, Muhammad; Hassan, Musheerul; et al. (Frontiers in Veterinary Science, 2024)
Introduction The utilization of fauna and fauna-based byproducts in ethnomedicinal usages has been a longstanding human activity, practiced across various cultures worldwide. This study focuses on investigating the utilization of animal-based traditional medicine by the people of Pakistan, specifically in the Gujranwala area. Methods Data collection took place from January to September 2019 through interviews with local communities. Ethnomedicinal applications of animal products were analyzed using several indices, including Relative Frequency of Citation (RFC), Relative Popularity Level (RPL), Folk Use Value (FL), and Relative Occurrence Percentage (ROP). Results The study identified the use of different body parts of 54 species of animals in treating various diseases and health issues. These include but are not limited to skin infections, sexual problems, pain management (e.g., in the backbone and joints), eyesight issues, immunity enhancement, cold, weakness, burns, smallpox, wounds, poisoning, muscular pain, arthritis, diabetes, fever, epilepsy, allergies, asthma, herpes, ear pain, paralysis, cough, swelling, cancer, bronchitis, girls’ maturity, and stomach-related problems. Certain species of fauna were noted by informers with high “frequency of citation” (FC), ranging from 1 to 77. For instance, the black cobra was the most frequently cited animal for eyesight issues (FC = 77), followed by the domestic rabbit for burn treatment (FC = 67), and the Indus Valley spiny-tailed ground lizard for sexual problems (FC = 66). Passer domesticus and Gallus gallus were noted to have the highest ROP value of 99. Discussion The findings of this study provide valuable preliminary insights for the conservation of fauna in the Gujranwala region of Punjab, Pakistan. Additionally, screening these animals for medicinally active compounds could potentially lead to the development of novel animal-based medications, contributing to both traditional medicine preservation and modern pharmaceutical advancements.